1997
DOI: 10.1007/bf00946939
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between endothelin-1-induced peripheral microvascular vasoconstriction and blood pressure in glaucoma patients

Abstract: Abstract• Background: The potent vasoconstrictor peptide endothelin-I has been shown to participate in the control of peripheral vascular tone and in the regulation of ocular perfusion. In glaucoma patients vasospasms and arterial hypotension have been identified as risk factors for the progression of glaucomatous damage, and the regulation of endothelin-1 release is disturbed in some of these patients. The aim of this study was to assess the relationship between resting blood pressure and cutaneous vascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…7 Finally, the vascular response to ET-1 has been shown to be enhanced in subcutaneous resistance arteries from patients with NTG, 25 and glaucoma patients with lower blood pressure values react more sensitively to ET-1. 26 As a result of vascular events, ET may in turn have further vascular effects, including ET A mediated rapid vasoconstriction and ET B induced vasodilation mediated by nitric oxide and possibly TNF-a, 27 28 but increased ET-1 levels may also exert direct receptor mediated effects on retinal ganglion cells and resident glial cells. Retinal ganglion cell loss in glaucomatous optic neuropathy is associated with a disruption in anterograde axonal transport.…”
Section: Discussionmentioning
confidence: 99%
“…7 Finally, the vascular response to ET-1 has been shown to be enhanced in subcutaneous resistance arteries from patients with NTG, 25 and glaucoma patients with lower blood pressure values react more sensitively to ET-1. 26 As a result of vascular events, ET may in turn have further vascular effects, including ET A mediated rapid vasoconstriction and ET B induced vasodilation mediated by nitric oxide and possibly TNF-a, 27 28 but increased ET-1 levels may also exert direct receptor mediated effects on retinal ganglion cells and resident glial cells. Retinal ganglion cell loss in glaucomatous optic neuropathy is associated with a disruption in anterograde axonal transport.…”
Section: Discussionmentioning
confidence: 99%
“…39 Normal peripheral vascular response to the E-1 is also altered in some individuals with glaucoma. 88 Intravitreal injections of E-1 into the rabbit eye produce marked effects on the anterior ciliary circulation, as well as constriction of the retinal vasculature. 89 With E-1 administration to the retrobulbar perineural space, localized constriction in the posterior ciliary arterial circulation has been produced, in both the rabbit and primate eye.…”
Section: Endothelial Factors (Endothelins)mentioning
confidence: 99%
“…In the present report, we described a rare case of Buerger's disease associated with NTG. Many factors have been suggest- ed in the literature as a possible major etiology of NTG, such as the autoimmune mechanism (Cartwright et al 1992;Maruyama et al 2000), vasospasm (Cartwright et al 1992), endothelin-1-related microvascular dysfunction (Gass et al 1997), and platelet hyperaggregation (Matsumoto et al 2001). In contrast, local ocular blood flow disturbance within the optic nerve head, associated with Buerger's disease, may have caused the glaucomatous optic neuropathy in our present case.…”
Section: Discussionmentioning
confidence: 61%
“…Although the precise pathological mechanisms causing NTG are still unknown, many investigators have reported that several kinds of factors may be involved in the etiology of NTG, including an autoimmune mechanism (Cartwright et al 1992;Maruyama et al 2000), vasospasm (Cartwright et al 1992), endothelin-1-related microvascular dysfunction (Gass et al 1997), platelet hyperaggregation (Matsumoto et al 2001). Clinically, the optic disc hemorrhages are recognized more frequently in patients with NTG than those with primary OAG (Hendrickx et al 1994).…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%